Dry reforming of methane for hydrogen production over NiâCo catalysts: Effect of NbâZr promoters - Abd Ghani, N.A. (Elsevier Ltd, 2018)
Ni/Al2O3, NiâCo/Al2O3âMgO and NiâCo/Al2O3âMgO/NbâZr nanocatalysts were prepared by the sol-gel technique with citric acid and tested in the dry reforming of methane (DRM). In this paper, the effects of Nb and Zr addition as promoters in Al2O3âMgO supported catalysts on the physicochemical characteristics and the reaction performance in the DRM were investigated. The NbâZr promoters are expected to enhance the activity and performance of the catalyst due to its high thermal stability and also improvement in the metal dispersion of the catalyst. The catalysts samples were characterized by FESEM, BET, XRD, TEM, H2-TPR and CO2-TPD techniques. FESEM results demonstrated that NiâCo/Al2O3âMgO/NbâZr has more uniform and well-dispersion of metal than NiâCo/Al2O3âMgO. The BET results unravel that the addition of NbâZr promoters increase the surface area of the synthesized catalyst due to the high surface area of the promoters. There is a formation of MgAl2O4 spinel-type solid solution proved by the XRD and CO2-TPD analysis due to the interaction between alumina lattice and magnesium metal which has high resistance to carbon formation. The DRM reaction is performed in the tubular furnace reactor at 1073.15 K, 1 atm and a CH4/CO2 ratio of unity. The sol-gelled NiâCo/Al2O3âMgO/NbâZr was found to be the most proper choice for DRM which illustrates much higher conversion (86.96 for CH4 conversion and 87.84 for CO2 conversion) compared to the other catalysts. This is due to the strong interaction between active metals and supports, resistance to coke formation and higher stability in DRM reaction. Â© 2018 Hydrogen Energy Publications LLC